2022
DOI: 10.1182/blood.2022016196
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following treatment for ADA-deficient severe combined immunodeficiency: a report from the PIDTC

Abstract: Adenosine deaminase (ADA) deficiency causes ∼13% of cases of severe combined immune deficiency (SCID). Treatments include enzyme replacement therapy (ERT), hematopoietic cell transplant (HCT), and gene therapy (GT). We evaluated 131 patients with ADA-SCID diagnosed between 1982 and 2017 who were enrolled in the Primary Immune Deficiency Treatment Consortium SCID studies. Baseline clinical, immunologic, genetic characteristics, and treatment outcomes were analyzed. First definitive cellular therapy (FDCT) inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Trials with lentiviral vectors report no mutagenesis to date with follow-up at 4–5 years post treatment. 25 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials with lentiviral vectors report no mutagenesis to date with follow-up at 4–5 years post treatment. 25 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…1 , 10 , 11 , 23 An update to the 2012 publication was published in 2022 and reported that for ADA SCID patients treated by HSCT or gene therapy after 2000 who had no active infection at the time of treatment there was no difference in five-year event-free survival or overall survival regardless of ERT use or pretreatment regimen. 25 …”
Section: Hematopoietic Stem Cell Transplantmentioning
confidence: 99%
“…These excellent results prompt a reconsideration of the hierarchy of treatment options, which needs to be supported by long-term studies comparing HSCT and GT outcomes. A recent report comparing HSCT and viral mediated gene addition outcomes, preceded or not by ERT, in 131 ADA-SCID patients [160] showed higher five-year overall and event-free survival rates in patients receiving ERT-GT (100%, 75.3%) than ERT-HSCT (79.6%, 73%) and HSCT (72.5%, 49.5%). Excellent and comparable survival rates were found between viral mediated gene addition and patients treated by MSD-HSCT and without infection.…”
Section: Viral Mediated Gene Addition and Gene Editing Approaches For...mentioning
confidence: 99%
“…Excellent and comparable survival rates were found between viral mediated gene addition and patients treated by MSD-HSCT and without infection. Moreover, alternative donor HSCT (particularly HLA-matched unrelated donor and cord blood) for young infants without infection should be considered an alternative when MSD/MFD HSCT and viral mediated gene addition are not available [160] .…”
Section: Viral Mediated Gene Addition and Gene Editing Approaches For...mentioning
confidence: 99%
“…Based on data on HSCT performed between 1981 and 2009 in 16 centers worldwide, an overall survival rate (OS) in ADA-SCID depends on type of HSCT, being 86% for MSD, 81% for MFD, 66% for MUD and 43 for Haplo(13). Recent studies on large groups of patients: 131 ADA-SCID diagnosed in 1982-2017(14) and 152 patients with SCID, including 43 ADA-SCID treated in 2006-2014(15), showed higher OS in patients transplanted from MSD/MFD under 3.5 months of age and without active infections. According to the European Society for Immunodeficiencies (ESID), the European Society for Blood and Marrow Transplantation (EBMT), and European Reference Network on Rare Primary Immunodeficiency Autoinflammatory Autoimmune diseases (RITA), gene therapy should be considered in absence of a matched family donor (…”
mentioning
confidence: 99%